Body Mass Index and Breast and Cervical Cancer Screening - Elfreda Samman; Rahma Mkuu; Xiaoying Zhang; Shelby Scummings; James Burdine (Women's Health Reports, 2022)
Background: Breast and cervical cancer screening are responsible for dramatically reducing cancer deaths. Overweight and obesity are associated with deleterious health outcomes, including increased risk of developing cancer. This study adds to the existing literature examining the association of having overweight and obesity and receipt of breast or cervical cancer screening. Methods: Using the 2013 Brazos Valley Community Health Needs Assessment, we examined the association between body mass index (BMI) and receipt of breast or cervical cancer screening among women meeting age recommendations for breast cancer and cervical cancer screening (n?=?1979 and n?=?2040), respectively. We used SPSS 22 statistical software for descriptive and logistic regression analysis. Results: Overall, 26.6% of women missed the breast cancer screening guidelines, and 13.3% missed the cervical cancer screening guidelines. BMI had a weak association with missing cervical cancer screenings (odds ratio [OR]?=?1.02; confidence interval [CI]?=?1.01?1.04), but no association with missing breast cancer screenings (OR?=?1.01; CI?=?0.99?1.03). Higher age, race (non-White), rural area, no health insurance, smoking, and delayed health care were associated with missing breast cancer screenings. Higher age, marital status (single), lower education, no health insurance, smoking, and delayed health care were associated with missing cervical cancer screening. Further research is needed to better understand the association using larger, more diverse samples.